Answer:
Shift the graph of f(x) 4 units to the right
and 7 units up
Explanation:
f(x) + n - shift a graph of f(x) n units up
f(x) - n - shift a graph of f(x) n units down
f(x + n) - shift a graph of f(x) n units to the left
f(x - n) - shift a graph of f(x) n units to the right
=============================================
We have
![f(x)=x^2,\ g(x)=x^2+(-8x)+7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1icmcudry97olok61bnoeg1pprat7ce27e.png)
Convert the equation of g(x) to the vertex formula:
![y=a(x-h)^2+k](https://img.qammunity.org/2020/formulas/mathematics/high-school/7xiq973pej7bis77rj649g420rebwvc4wx.png)
![g(x)=x^2+(-8x)+7\\\\g(x0=x^2-2(x)(4)+7\\\\g(x)=\underbrace{x^2-2(x)(4)+4^2}-4^2+7\qquad\text{use}\ (a-b)^2=a^2-2ab+b^2\\\\g(x)=(x-4)^2+7=f(x-4)+7\\\\\text{shift the graph of f(x) 4 units to the right and 7 units up}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2gxse8uvexycwzkfxpcw4k7aaebug0hrcw.png)